Contemplation and Craft in Turkish Material Arts (American Journal of Islam and Society, 2016)
Books Reviewed: Mehmet Zeki Kuşoğlu, The Ottoman Touch: TraditionalDecorative Arts and Crafts (Istanbul: Blue Dome Press, 2015); Mehmet ZekiKuşoğlu, Silver in Turkish Art (Istanbul: Blue Dome Press, 2015); Sema Onat,Islamic Art of Illumination: Classical Tazhib from Ottoman to ContemporaryTimes (Istanbul: Blue Dome Press, 2015); Laurelie Rae, Islamic Art and Architecture:Memories of Seljuk and Ottoman Masterpieces (Istanbul: BlueDome Press, 2015).The unusual aspect connecting these four books is not the fact that they sharethe same publisher or even the same general scope of Turkish arts, but thatthey have been authored by practicing artists who have featured some of theiroriginal works between their covers.Blue Dome Press, a relatively new publisher, has offices in the majorwestern cities; however, all of the printing done in Istanbul. In addition, themajority of its publications, which range from Turkish cooking to fiction, fromcurrent affairs to various arts, focus on some aspect of Turkish culture. Bysupporting the publication of these texts, one gets the sense that various sectorsof Turkish society continue to value the traditional and important historicalcontributions that the featured and other contemporary artists continue to maketo the national culture.The three artists featured in this review (one is the author of two books)come from different backgrounds that have enabled them to practice their arttoday. Mehmet Zeki Kuşoğlu author of The Ottoman Touch: Traditional DecorativeArts and Crafts and Silver in Turkish Art, has practiced the crafts ofsilverwork and other art forms based on traditional methods for over fortyyears. During his career, he has apprenticed with craftsmen – he identifiesthem by name – and completed two art degrees in Turkey. His efforts to understand,reconcile, and ultimately interpret the country’s historical craft methodsthrough his own creations lends a tremendous insight into the meaningsand processes of crafts, one that brings them palpably alive. Sema Onat, author ...